Indução de calos e potencial embriogênico em bastão do imperador - Dias, Gabrielen de Maria Gomes (2010)
The species Etlingera elatior (Jack) R.M. Smith, popularly known as torch ginger, is an ornamental plant with excellent marketing potential. The method of division propagation by rhizome division produces a small number of seedlings. In this manner, protocols aiming at the in vitro massal propagation via embryogenesis, appear as important alternatives. The objective of this work was to propose methodologies for the in vitro cultivation of torch ginger, by means of the somatic embryogenesis induction. For the first work, rhizome segments and their position in the culture medium and inoculated in a medium supplemented with 10µM of ANA, AIA, AIB, picloram, 2,4-D and without auxin were tested. They were evaluated at 50 days as to the percentage of callus induction. The results pointed out that the MS medium added of 10µM of 2,4-D and the inoculated rhizome at the upright position were those which presented the highest percentage (100%) of embryogenic callus induction. In the second work, the explants consisted of rhizome, leaf and root segments and were inoculated in medium supplemented with both 2,4-D and picloram at the concentrations of (0.0; 1.0; 2.0; 4.0 mg L-1). At120 days, the evaluation was performed with relation to the percentage of callus induction. The results pointed out that the culture medium with 2,4-D provided the induction of calluses with embryogenic characteristics on rhizome segment explants. Use of 2,4-D and picloram resulted into the formation of calluses on the different explants, but increased amount of somatic embryos in the media supplemented with 2,4-D was found. In the ultrastrucutural analysis of the calluses with embryogenic characteristics, it was found that the cells possessed isodiametric shape similar to somatic embryos at the globular stage and the cytochemial analysis, the presence of the mass of the proembryogenic-celled callus on the explants grown in the culture media containing both regulators could be confirmed. Those calluses were later analyzed in the flux cytometer at 160 days, where it was found that the calluses induced by the growth regulator 2,4-D minus mixoploids in relation to picloram. The results indicate a variation in the level of ploidy of calluses generated from rhizome segment explants. So, the source of explant and the integrity of this have a direct relationship in the mitotic variation of the torch ginger.